Estimated Glycation End Products and Oxidative Status in Renal Failure Patients - Salam Khalid Mutlag; Mohanad Hammo Mukhlif1 (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The present study conducted to assess the Glycation end products and oxidative status of in patients with renal failure. 100 patients that have had CKD for less than 2 years have been diagnosed by a doctor. A control group of 40 stable individuals was selected. From October 2021 to February 2022, patients were confirmed to be sick with chronic renal disease at Azadi Teaching Hospital and Al-Jumhuri Hospital. ‎the results showed that the largest age group of patients was > 60 years with percent (39%). Body Mass Index (BMI) of patients was 18.5-24.9 kg with percent (52%). Residential Area of patients was urban with percent (83%). Smoking Status of patients was non-smoking with percent (68%). The current outcomes demonstrated a reduction in the concentration of total protein that is significant (P<0.05), albumin and globulin in patients compare with healthy volunteers. On the other hand, the results show a significant (P<0.05) elevated in levels of carbonyl and amino group, while decreased in thiol levels in patients compare with healthy volunteers. Otherwise, the Glycation level shows significant (P<0.05) elevated in in patients compare with healthy volunteers. Its concluded that the CKD lead to elevated Glycation level and changes in oxidative status.